Functional topography of the right inferior parietal lobule structured by anatomical connectivity profiles. Issue 12 (13th July 2016) - Wang, Jiaojian; Zhang, Jinfeng; Rong, Menglin; Wei, Xuehu; Zheng, Dingchen; Fox, Peter T.; Eickhoff, Simon B.; Jiang, Tianzi
Abstract: The nature of the relationship between structure and function is a fundamental question in neuroscience, especially at the macroscopic neuroimaging level. Although mounting studies have revealed that functional connectivity reflects structural connectivity, whether similar structural and functional connectivity patterns can reveal corresponding similarities in the structural and functional topography remains an open problem. In our current study, we used the right inferior parietal lobule (RIPL), which has been demonstrated to have similar anatomical and functional connectivity patterns at the subregional level, to directly test the hypothesis that similar structural and functional connectivity patterns can inform the corresponding topography of this area. In addition, since the association between the RIPL regions and particular functions and networks is still largely unknown, post‐hoc functional characterizations and connectivity analyses were performed to identify the main functions and cortical networks in which each subregion participated. Anatomical and functional connectivity‐based parcellations of the RIPL have consistently identified five subregions. Our functional characterization using meta‐analysis‐based behavioral and connectivity analyses revealed that the two anterior subregions (Cl1 and Cl2) primarily participate in interoception and execution, respectively; whereas the posterior subregion (Cl3) in the SMG primarily participates in attention and action inhibition. The two posterior subregions (Cl4, Cl5) in the AG were primarily involved in social cognition and spatial cognition, respectively. These results indicated that similar anatomical and functional connectivity patterns of the RIPL are reflected in corresponding structural and functional topographies. The identified cortical connectivity and functional characterization of each subregion may facilitate RIPL‐related clinical research. Hum Brain Mapp 37:4316–4332, 2016 . ©2016 Wiley Periodicals, Inc.